ANALISIS FAKTOR-FAKTOR PEMBERIAN OPINI AUDIT GOING CONCERN ( Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2010 - 2012 ) - Noviandhi Resilla; Muhammad Rasuli; Edfan Darlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to test and prove empirical evidence of: The effect of Profitability, Liquidity, and Solvability with the acceptance of Going Concern Audit Opinion (OGC). The populations in this study was manufacturing companies with listed in Indonesia Stock Exchange at 2010- 2012. The samples was selected by using purposive sampling method. The data was analysed by using logistic regression analysis with SPSS version 17.0. Based on the result of test Profitability and Liquidity have an effect to acceptance of Going Concern Audit Opinion while variable Solvability not have an effect to acceptance of Going Concern Audit Opinion (OGC).Keywords: Profitability, Liquidity, Solvability, and Going Concern Audit Opinin (OGC).